Інтеграція розрізнених даних про клієнта з використанням інтелектуального агента визначення структури джерела - Шаховська, Н.Б.; Угрин, Д.І. (Моделювання та інформаційні технології, 2009)
Аn order, methods and facilities of getting, concordance, integration of client
information, creation of operative depositories of information and load of information,
is in-process worked out in a central depository.